Ergonomic Analysis Of Home-Based Beverage And Snack Stalls In The Krembangan And Simokerto Districts Of Surabaya City - Titis Nabila Maharani; Yura Witsqa Firmansyah (Journal of Health Management Research, 2026)
Background : Ergonomics is the science of studying the fit between workers, equipment, work methods, and the work environment to create safe, comfortable, healthy, and efficient working conditions. Home-based beverage and snack stalls are a type of micro-enterprise still dominated by manual work activities, thereby posing a potential risk of musculoskeletal disorders (MSDs). Aims: This study aims to analyze ergonomic risks associated with work activities at home-based beverage and snack stalls. A descriptive observational method was employed, conducted at two stalls located at Sedayu street Gang 1 No. 55 Krembangan subdistrict and Gembong street Gang 5 Simokerto subdistrict Surabaya city on, involving five respondents. Data collection was carried out through direct observation and documentation of work activities. Results and Discussion: The results identified five main activities involving ergonomic risks: scooping ice cubes, preparing drinks, lifting LPG cylinders, peeling ingredients, and frying snacks. The activity of scooping ice cubes yielded the highest risk score (16), followed by lifting LPG cylinders (10), frying snacks (9), preparing drinks (6), and peeling ingredients (4). Identified risk factors included stooping postures, static standing, repetitive movements, and manual load lifting. Conclusion: Ergonomic improvements such as workspace reorganization, adjustment of table and storage container heights, implementation of proper Manual Material Handling (MMH) techniques, and the provision of scheduled stretching breaks are expected to reduce MSD risks and enhance worker safety, comfort, and productivity.